2011
DOI: 10.1007/s11661-011-0705-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Deformation Response of β-Annealed Ti-5Al-5V-5Mo-3Cr Alloy Under Compressive Loading Conditions

Abstract: This article reports the cyclic deformation behavior of the b-annealed metastable Ti-5Al-5V-5Mo-3Cr (Ti-5553) alloy under the condition of pure compressive fatigue stress. The following three aspects, namely, the mechanical response, the surface morphology evolution, and the dislocation structures, were systematically investigated. Under all testing conditions, the material demonstrated cyclic softening in the initial cycles followed by saturation. The progressive observation of surface morphology at fixed loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…Dislocation configurations indicate the planar slip in cyclic deformation of a phase, which is also reported in other titanium alloys [11,12]. The researchers suggest that the lower SFE, appropriate SRDs and the higher e/a ratio may cause planar slip in deformation of Ti-5553 alloy [12].…”
Section: Characteristics Of Deformation Crack Initiation and Propagasupporting
confidence: 53%
See 1 more Smart Citation
“…Dislocation configurations indicate the planar slip in cyclic deformation of a phase, which is also reported in other titanium alloys [11,12]. The researchers suggest that the lower SFE, appropriate SRDs and the higher e/a ratio may cause planar slip in deformation of Ti-5553 alloy [12].…”
Section: Characteristics Of Deformation Crack Initiation and Propagasupporting
confidence: 53%
“…It is well known that microstructure has a significant effect on fatigue behavior of titanium alloys [8][9][10][11][12][13][14][15][16]. The fatigue strength decreases in the order of bimodal, lamellar (Widmannstatten) and equiaxed microstructure in Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 99%
“…10d displays that lots of deformation twins with size of about 50nm in widths are produced in α phase. It has been reported that deformation twins will be induced in many metals when the dislocation slip is not sufficient to accommodate the cyclic plastic deformation [6,[9][10][33][34]. In general, assuming everything else is equal, fatigue crack tends to nucleate in coarse grained material than the fine grained materials [6].…”
Section: Cracks Propagationmentioning
confidence: 99%
“…The advantage of this alloy as compared to other β titanium alloys is the sluggish precipitation kinetics of the α phase [5,6]. Ti5553 offers high strength, excellent hardenability, fracture toughness as well as high fatigue resistance [7]. The potential applications of this alloy are in the high-strength related areas such as landing gear and pylon/nacelle areas.…”
Section: Introductionmentioning
confidence: 99%